2019
DOI: 10.1021/acsami.9b05214
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Dual Temperature–Pressure Sensing and Parameter Self-Separating Based on Ionic Hydrogel via Multisynergistic Network Design

Abstract: Hydrogel-based wearable sensors have experienced an explosive development, whereas functional integration to mimic the multisignal responsiveness of skin especially for pressure and temperature remained a challenge. Herein, a functional ionic hydrogel-base flexible sensor was successfully prepared by integrating the thermal-sensitive N-isopropylacrylamide (NIPAAm) into another conductive double-network hydrogel based on polyvinyl alcohol–graphene oxide (PVA–GO) and polyacrylic acid–Fe3+ (PAA–Fe3+). Because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(76 citation statements)
references
References 38 publications
2
74
0
Order By: Relevance
“…[31,32] In recent years, water-rich, soft, and 3D network hydrogels have spout out in the field of flexible sensors. [33][34][35][36][37] However, some problems remain to be solved: i) the physical cross-linking networks are often fragile and cannot meet the requirements of larger deformation while the chemical cross-linking hydrogels, once the chemical bonding is destroyed, are difficult to restore the original structure. [38] ii) Due to the lack of adhesion, adhesive tapes such as 3M tape, are required to attach the hydrogel sensors to the skin, which influences the measurement process of the sensors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[31,32] In recent years, water-rich, soft, and 3D network hydrogels have spout out in the field of flexible sensors. [33][34][35][36][37] However, some problems remain to be solved: i) the physical cross-linking networks are often fragile and cannot meet the requirements of larger deformation while the chemical cross-linking hydrogels, once the chemical bonding is destroyed, are difficult to restore the original structure. [38] ii) Due to the lack of adhesion, adhesive tapes such as 3M tape, are required to attach the hydrogel sensors to the skin, which influences the measurement process of the sensors.…”
Section: Introductionmentioning
confidence: 99%
“…[39] Zhang and co-workers prepared mechanically recoverable flexible sensors by integrating the thermal-sensitive N-isopropylacrylamide (NIPAAm) into another conductive double-network hydrogel based on polyvinyl alcohol-graphene oxide (PVA-GO) and polyacrylic acid-Fe 3+ (PAA-Fe 3+ ). [34] Inspired by nature, Shen's group combined natural sea urchin-like microcapsules with 2D MXene nanoflakes to prepare a flexible pressure sensor that was 8.69 times more sensitive than the sensor with a planar structure. [40] In this work, a ternary system hydrogel consists of silk fibroin (SF), acrylamide (AM) and acrylic acid (AA) is prepared by one-pot thermal polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…reported. For instance, multiple-network hydrogels, such as triple-network hydrogels, [482,483] DN-NC hydrogels, [484][485][486] anisotropic liquid crystalline DN hydrogels, [487,488] void-DN hydrogels, [489] and microgel-reinforced DN hydrogels. [89,490,491] Suo's group formed a type of highly stretchable and tough DN hydrogels that had combined ionically and covalently crosslinked networks.…”
Section: Figure 14 Schematic Illustrations Of An Sipn (A) and A Fipn (B)mentioning
confidence: 99%
“…However, acrylic hydrogels are very brittle, which is a big problem in building smart devices [35]. Therefore, many studies have been reported on improving the mechanical properties of polyacrylic acid hydrogels to prepare smart devices, such as flexible sensors [36,37]. Herein, in the process of polymerization of acrylic acid and hydroxyethyl acrylate monomers into hydrogels, we added graphene oxide to a prehydrogel solution to prepare pH-responsive conductive hydrogels, which have high conductivity.…”
Section: Introductionmentioning
confidence: 99%